Ciaran Carson : space, place, writing - Alexander, Neal (Liverpool English texts and studies, 2010)
Ciaran Carson is one of the most challenging and inventive of contemporary Irish writers, exhibiting verbal brilliance, formal complexity, and intellectual daring across a remarkably varied body of work. This study considers the full range of his oeuvre in poetry, prose, and translations.